Anxiety intensity and elements stability on the beam: A IZOF application - Zheng, J.; Cai, G.; Yuan, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Although previous research which has examined IZOF has revealed that athletes do maintain a unique emotion-related performance zone, this research is limited by a number of factors: 1) the results were derived from self-report measures only; 2) the traditional methods used to determine IZOF also contain several weaknesses. The current investigation involves a multimodal assessment including self-reports, behavioural observations and physiological measurements [1]. Probabilistic estimation has been shown to have more correct classifications within the zones and fewer incorrect classifications outside the zones and therefore the application of the probabilistic method is also investigated.